Driving factor of sustainable environmental manufacturing practices in Malaysia - Adebambo, Hameed O.; Ashari, Hasbullah; Nordin, Norani (2014)
An increased demand has been placed on the manufacturing industries to be more responsible to their environment with respect to their operational activities.This demand is due to various antecedent factors driving sustainable environmental practices in manufacturing firms. This study therefore, investigated the factors that drive the sustainable environmental practices in Malaysian manufacturing sector. Survey questionnaire was used to collect data from 103 manufacturing firms and was analyzed using PLS path modelling technique. The result of the study found that top management commitment and stakeholder pressure significantly influence sustainable environmental manufacturing practices while public concern did not show significant evidence.